METABOLIC REPROGRAMING OF ADOPTIVELY TRANSFERRED T CELLS TO POTENTIATE ANTITUMOR RESPONSE - RODRIGUEZ, Paulo C; WANG, Yunfei; HWU, Patrick; DOMINGUEZ, Ana Lucia; MANRIQUE, Soraya Zorro (2024)
Disclosed herein are immune effector cells for use in adoptive cell transfer that have chemically- or genetically-inhibited PDHB (Pyruvate dehydrogenase E1 subunit beta) expression or activity. Also disclosed are methods of inhibiting or ablating PDHB expression in immune effector cells ex vivo and methods of using these cells to treat subjects with cancer. In some embodiments, the immune effector cells are further treated with a TIMS inhibitor or gendtically engineered to ablate TIM3 expression. In some embodiments, the immune effector cells are further treated with a LAGS inhibitor or genetically engineered to ablate LAG3 expression. In some cases, the PDHB gene is disrupted by insertion of the gene encoding the chimeric receptor into the PDHB gene loci of the cell. Therefore, disclosed herein is a chimeric cell expressing a chimeric receptor. L'invention concerne des cellules effectrices immunitaires destinées à être utilisées dans le transfert adoptif de cellules qui ont une expression ou une activité de PDHB (Pyruvate déshydrogénase E1) inhibée chimiquement ou génétiquement. L'invention concerne également des procédés d'inhibition ou d'ablation de l'expression de PDHB dans des cellules effectrices immunitaires ex vivo et des procédés d'utilisation de ces cellules pour traiter des sujets atteints d'un cancer.